A quantitative study of white matter hypomyelination and oligodendroglial maturation in focal cortical dysplasia type II. Issue 5 (28th March 2013) - Shepherd, Caterina; Liu, Joan; Goc, Joanna; Martinian, Lillian; Jacques, Thomas S.; Sisodiya, Sanjay M.; Thom, Maria
Summary Purpose A diagnostic feature of focal cortical dysplasia (FCD) type II on magnetic resonance imaging (MRI) is increased subcortical white matter (WM) signal on T2 sequences corresponding to hypomyelination, the cause of which is unknown. We aimed to quantify WM pathology in FCD type II and any deficiency in the numbers and differentiation of oligodendroglial (OL) cell types within the dysplasia. Methods In 19 cases we defined four regions of interests (ROIs): ROI1 = abnormal WM beneath dysplasia, ROI2 =dysplastic cortex, ROI3 = normal WM, and ROI4 = normal cortex. We quantified axonal and myelin density using immunohistochemistry for neurofilament, myelin basic protein and quantified mature OL with NogoA, cyclic nucleotide 3‐phosphodiesterase (CNPase) and OL precursor cell (OPC) densities with platelet derived growth factor receptor (PDGFR)α, β and NG‐2 in each region. Key Findings We observed a significant reduction in myelin and axons in the WM beneath dysplasia relative to normal WM and there was a correlation between relative reduction of myelin and neurofilament in each case. OL and OPC were present in the WM beneath dysplasia and although present in lower numbers with most markers, were not significantly different from normal WM. Neurofilament and myelin labeling highlighted disorganized orientation of fibers in dysplastic cortex but there were no significant quantitative differences compared to normal cortex. Clinical correlations showed an association between the severity of reduction of myelin and axons in the WM of FCD and duration of epilepsy. Significance These findings indicate a reduction of myelinated axons in the WM of FCD type II rather than dysmyelination as the primary pathologic process underlying WM abnormalities, possibly influenced by duration of seizures. The range of OPC to OL present in FCD type II does not implicate a primary failure of cell recruitment and differentiation of these cell types in this pathology.